Use of High-Dose Nebulized Colistimethate in Patients with Colistin-Only Susceptible Acinetobacter baumannii VAP: Clinical, Pharmacokinetic and Microbiome Features - Gennaro De Pascale; Gabriele Pintaudi; Lucia Lisi; Flavio De Maio; Salvatore Lucio Cutuli; Eloisa Sofia Tanzarella; Simone Carelli; Gianmarco Lombardi; Melania Cesarano; Veronica Gennenzi; Gabriella Maria Pia Ciotti; Domenico Luca Grieco; et al. (MDPI AG, 2023)
(1) Background: Colistin-only susceptible (COS) Acinetobacter baumannii (AB) ventilator-associated pneumonia (VAP) represents a clinical challenge in the Intensive Care Unit (ICU) due to the negligible lung diffusion of this molecule and the low-grade evidence on efficacy of its nebulization. (2) Methods: We conducted a prospective observational study on 134 ICU patients with COS-AB VAP to describe the 'real life' clinical use of high-dose (5 MIU q8) aerosolized colistin, using a vibrating mesh nebulizer. Lung pharmacokinetics and microbiome features were investigated. (3) Results: Patients were enrolled during the COVID-19 pandemic with the ICU presenting a SAPS II of 42 [32-57]. At VAP diagnosis, the median PaO2/FiO2 was 120 [100-164], 40.3% were in septic shock, and 24.6% had secondary bacteremia. The twenty-eight day mortality was 50.7% with 60.4% and 40.3% rates of clinical cure and microbiological eradication, respectively. We did not observe any drug-related adverse events. Epithelial lining fluid colistin concentrations were far above the CRAB minimal-inhibitory concentration and the duration of nebulized therapy was an independent predictor of microbiological eradication (12 [9.75-14] vs. 7 [4-13] days, OR (95% CI): 1.069 (1.003-1.138), p = 0.039). (4) Conclusions: High-dose and prolonged colistin nebulization, using a vibrating mesh, was a safe adjunctive therapeutic strategy for COS-AB VAP. Its right place and efficacy in this setting warrant investigation in interventional studies.